2006
DOI: 10.1039/b514528g
|View full text |Cite
|
Sign up to set email alerts
|

A versatile template for the formation of [2]pseudorotaxanes. 1,2-Bis(pyridinium)ethane axles and 24-crown-8 ether wheels

Abstract: Linear 1,2-bis(pyridinium)ethane 'axles' and macrocyclic 24-membered crown ether 'wheels' (, and ) combine to form [2]pseudorotaxanes. These interpenetrated adducts are held together by N+...O ion-dipole interactions, a series of C-H...O hydrogen bonds and pi-stacking between electron-poor pyridinium rings of the axle and electron-rich catechol rings of the wheel. 1H NMR spectroscopy was used to identify the structural details of the interaction and to determine the thermodynamics of the binding process in sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 78 publications
7
63
1
Order By: Relevance
“…As expected, there was a substantial increase in association constant upon benzylation; from 8.0 10 1 to 2.3 10 3 m À1 comparing DB24C8 to DSDB24C8 2À . These values compare well to those observed for similar systems [14] and verify that [2&DSDB24C8] À should be capable of acting as a pseudorotaxane linker between metal ions in a MORF.…”
Section: Resultssupporting
confidence: 83%
“…As expected, there was a substantial increase in association constant upon benzylation; from 8.0 10 1 to 2.3 10 3 m À1 comparing DB24C8 to DSDB24C8 2À . These values compare well to those observed for similar systems [14] and verify that [2&DSDB24C8] À should be capable of acting as a pseudorotaxane linker between metal ions in a MORF.…”
Section: Resultssupporting
confidence: 83%
“…2. 4 The strength of the non-covalent interactions could be controlled by varying the substituents on the axle pyridinium rings. In particular, an EWG provides increased hydrogen bonding and electrostatic interactions and therefore an increase in the stability of the system.…”
Section: The (12-bis(pyridinium)ethane)(24-crown-8) Templatementioning
confidence: 99%
“…Although recent papers described on one hand the use of the "click chemistry" as an efficient route to triazolrotaxanes [7] and on another hand the recognition study of anions by 1,2,3-triazolium receptors, [8] the N-methyltriazolium moiety has never been described as a molecular station for DB24C8 so far. However, since Busch et al reported the ability for the DB24C8 to interact strongly with ammonium cation, [9] a wide variety of other template moieties, such as benzylic ammonium, [10] N-benzylic anilinium, [11] N,N'-di-A C H T U N G T R E N N U N G alkyl-4,4'-bipyridinium, [12] 1,2-bis(pyridinium)ethane cations, [13] The already reported N-alkylanilinium was chosen as the templated moiety for the preparation of the [2]rotaxane 3, and, at the same time, as the best molecular station for DB24C8 in the targeted molecular machine 4. The cationic electron-poor aromatic ring N-methyltriazolium should be able to interact with the DB24C8 either by p-p stacking with the electron-rich catechol ring, by ion-dipole interactions between the cationic charge and the oxygens of the macrocycle or by hydrogen bond between the vinylic hydrogen of the triazolium and the oxygens of the macrocycle.…”
mentioning
confidence: 99%